Taxonomic position and identity of Stemodia scoparioides (Gratiolae, Plantaginaceae) - Sosa, Maria De Las Mercedes; Dematteis, Massimiliano (Phytotaxa, 2013)
In recent floristic and taxonomic studies, Stemodia scoparioides (Gratiolae, Plantaginaceae) has been considered a synonym of S. lanceolata or a synonym of S. stricta. However, a detailed analysis of the type material and additional specimens clearly indicates that this is a different species, which can be distinguished by the aspect of the plants, the size of the leaves, the shape of the blades, and the length of the corollas. Consequently, in this contribution Stemodia scoparioides is resurrected from the synonymy as an independent species based on the analysis of morphological features. Additionally, complete description (including the pollen grains), geographic distribution, ecological observations, and a key to distinguish the related species are also reported, together with an illustration of S. scoparioides.